Incised for eternity : the graffiti on the Second Stela of Kamose revisited - Flammini, Roxana (2021)
Fil: Flammini, Roxana. Pontificia Universidad Católica Argentina. Facultad de Ciencias Sociales. Instituto de Investigaciones; Argentina